Islamic perspective on management contemporary issues - Nor 'Azzah Kamri; Azian Madun; Suhaili Sarif (YaPEIM mangement Academy & Deoartment Syariah and Management, APIUM, 2013)
This bilingual book revisits and reviews the challenges of management from Islamic perspective in terms of its theory and practice. Looking back of what been achieved so far, the challenges of Islamic management and its implemention can continuously be analyzed and improved.